EFL Learners’ Listening Strategies and Self-Efficacy in Listening Comprehension: A Descriptive Quantitative Study - Chelsea Feriska Putri Munawar; Testiana Deni Wijayatiningsih; Riana Eka Budiastuti (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
Listening comprehension is a fundamental yet challenging skill for learners of English as a Foreign Language (EFL), as it requires real-time processing of spoken input and effective management of cognitive and affective factors. This study aims to describe EFL learners’ listening strategy use and self-efficacy in listening comprehension following listening strategy instruction. A descriptive quantitative research design was employed to capture learners’ reported behaviors and confidence levels in listening activities. The participants were undergraduate students enrolled in a listening-focused English course in an Indonesian higher education context. Data were collected using two close-ended Likert-scale questionnaires: a listening strategy questionnaire and a self-efficacy questionnaire. Descriptive statistical analysis, including frequencies and percentages, was used to illustrate patterns and tendencies in learners’ responses. The findings indicated that learners reported more frequent use of during-listening strategies, such as note-taking, focusing on key words, and monitoring comprehension, than pre-listening strategies, including predicting content and activating background knowledge. In terms of self-efficacy, learners demonstrated moderate to high confidence in understanding spoken English and persisting during listening tasks, although lower confidence was reported when dealing with unfamiliar vocabulary, fast speech, or unfamiliar accents. Overall, the results reveal variation in learners’ listening strategy use and self-efficacy within the same instructional context. The study highlights the importance of addressing both strategic awareness and learner confidence in EFL listening instruction.